The Effect of Animated Education and Cartoon Video on Children Anxiety during Intravenous Insertion - Komang Yogi Triana; Ni Made Ari Sukmandari; Made Pande Lilik Lestari (Universitas Aisyah Pringsewu, 2023)
Intravenous (IV) insertion is one of the most common invasive procedures that causes pain, fear, and even stress for children. Uncontrolled anxiety feeling can develop into excessive anxiety and create a permanent traumatic impact on a child's life. Children need to know about the procedure that they will face in interesting way. This study purpose to identify the effectiveness of providing information through animated educational media about IV insertion on children's anxiety responses. This quantitative research used quasy-experimental design approach to compare three intervention between Animated Educational Video, Cartoon Video and Control Group. The samples of this study were choosen by consecutive sampling which it starts on April until June 2022. It was conducted at emergency unit of three hospitals area in Bali Province. Total respondents were about 90 children divided into three groups. Data was collected using Children Fear's Scale (CFS) as the instrument. This study found that there was a significant difference between three intervention groups (p=0,008 p less than 0,05). The animated education video group showed lowest mean anxiety score (1.90) compared to other group interventions. The developed animated education video can be selected intervention to control the anxiety feeling of children during IV insertion. Abstrak: Insersi intravena (IV) adalah salah satu prosedur invasif paling umum yang menyebabkan rasa sakit, ketakutan, dan bahkan stres bagi anak-anak. Perasaan cemas yang tidak terkendali dapat berkembang menjadi kecemasan yang berlebihan dan menimbulkan dampak traumatis permanen pada kehidupan anak. Anak-anak perlu tahu tentang prosedur yang akan mereka hadapi dengan cara yang menarik. Penelitian ini bertujuan untuk mengetahui efektivitas pemberian informasi melalui media edukasi animasi pemasangan infus terhadap respon kecemasan anak. Penelitian kuantitatif ini menggunakan pendekatan quasy-experimental design untuk membandingkan tiga intervensi antara Video Edukasi Animasi, Video Kartun dan Kelompok Kontrol. Sampel penelitian ini dipilih dengan cara consecutive sampling yang dimulai pada bulan April hingga Juni 2022. Dilakukan di unit gawat darurat tiga rumah sakit di Provinsi Bali. Jumlah responden sekitar 90 anak yang dibagi menjadi tiga kelompok. Pengumpulan data dilakukan dengan menggunakan Children Fear's Scale (CFS) sebagai instrumennya. Penelitian ini menunjukkan bahwa ada perbedaan yang signifikan antara ketiga kelompok intervensi (p=0,008 p kurang dari 0,05). Kelompok video pendidikan animasi menunjukkan skor kecemasan rata-rata terendah (1,90) dibandingkan dengan intervensi kelompok lain. Video edukasi animasi yang dikembangkan dapat menjadi intervensi pilihan untuk mengontrol rasa cemas anak saat pemasangan infus.